Restless spatialities: SobreVivo, trajectories of a blackened creation (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
The paper reflects on the creative process of SobreVivo - Antes que o baile acabe, focusing on the dynamics of the spatial composition of the performance, considering its aesthetic, ethical, poetic, political and social aspects. The play addresses ethnical-racial themes through an anti-racist approach that seeks to build a blackened space, supported by black people cultural manifestations, such as funk, slam, samba and African-based religiosity, as well as African-centered notions, such as escrevivência and quilombism. The dramaturgy was devised by the group through biographical narratives evoking their experiences in terms of blackness and racism. The scene conceived is both critical and festive, questioning the social positions of the viewers.
Keywords: Theater; Anti-racism; Blackness; Festivity; Spatialities